Ответ:
[tex]3x^2y^3=5\ \ \ \Rightarrow \ \ y^3=\dfrac{5}{3x^2}[/tex]
Подставим это выражение вместо [tex]y^3[/tex] во второе выражение.
[tex]11x^6y^3=11x^6\cdot \dfrac{5}{3x^2}=\dfrac{55\, x^6}{3x^2}=\dfrac{55\, x^4}{3}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex]3x^2y^3=5\ \ \ \Rightarrow \ \ y^3=\dfrac{5}{3x^2}[/tex]
Подставим это выражение вместо [tex]y^3[/tex] во второе выражение.
[tex]11x^6y^3=11x^6\cdot \dfrac{5}{3x^2}=\dfrac{55\, x^6}{3x^2}=\dfrac{55\, x^4}{3}[/tex]